Dynamic Assessment of Self-Regulation and Planning Behavior - Tzuriel, David; Hanuka-Levy, Dikla; Kashy-Rosenbaum, Gaby (Frontiers in Education, 2022)
Dynamic assessment (DA) of self-regulation and planning behavior are neglected area of research. The objective of this study is to present a novel DA method of executive functions using the Seria-Think Instrument-Revised (STI-R). The reliability and validity the STI-R was examined with children in grades 3–6. Children were randomly assigned to an experimental (n = 85) and control (n = 85) groups and administered the STI-R and the Seriation Math Problems Test before and after the STI-R teaching phase. In the teaching phase children in the experimental group were taught problem-solving strategies while children in the control group received a substitute intervention. The STI-R yields four scores: performance, number of insertions (NINS, indicating impulsivity), number of measurements (NMES, indicating planning), and efficiency index (EFFIN). Children in the experimental group showed a significant decrease in NINS and an increase in performance, NMES, and EFFIN from pre- to post-teaching. In the transfer phase they showed higher performance and EFFIN and lower NINS than children in the control group. The findings indicate that NINS is negatively correlated with NMES and that the correlation between the pre- and post-teaching phases in all variables were lower in the experimental than in the control group. The typology of Reflective, Impulsive, Effective, and Non-effective children was also confirmed. Regression analysis showed that NINS significantly predicted math problem-solving score before and after teaching. The findings support the reliability and validity of the STI-R and that cognitive modifiability of executive functions is a promising domain of DA complementing DA of performance scores.